Konseling Pastoral Pada Orang Dengan HIV/AIDS Yang Mengalami Diskriminasi Dari Masyarakat - Oley, Deby Meilina (PT. Giat Konseling Nusantara, 2024)
The aim of this study is to analyze people with HIV/AIDS who have experienced discrimination in the Batamang Plus Foundation and describe a model of supporting pastoral counseling to people with AIDS who have been discriminated against. This research is qualitative research with case study methods implemented in the Batamang Plus Manado Foundation 2023. Data collected through observations, interviews, documentation, pastoral counseling, from the results of analysis and interpretation of data obtained indications that (1) People with HIV/AIDS are being discriminated against by their family and environment (2) Discrimination affects the irregular and mental emotions of people with HIV / AIDS. Based on the findings, in order to address the situation experienced by people with HIV/AIDS, the researchers performed a pastoral accompaniment of six meetings and as a result, subjects who were initially injured due to discrimination from family and environment can accept the reality and forgive the family and are more willing to accept themselves and not blame themselves and approach God. Thus it should be understood that the words and behavior to others must be consistent with knowledge and what is said must be compatible with the facts that do not judge or discriminate against others.